Does physician dispensing increase drug expenditures? - Boris Kaiser; Christian Schmid (University of Bern, Department of Economics, 2013)
We analyze whether the possibility for physicians to dispense drugs increases health care expenditures due to the incentives created by the markup on drugs sold. Using comprehensive physician-level data from Switzerland, we exploit the fact that there is regional variation in the dispensing regime to estimate policy effects. The empirical strategy consists of doubly-robust estimation which combines inverse-probability weighting with regression. Our main finding suggests that if dispensing is permitted, physicians produce significantly higher drug costs in the order of 30% per patient.
Keywords: I11; I18; C21; 330; health care costs; drug expenditures; physician dispensing; supply-induced demand; treatment effects.